Accuracy of physician assessment of treatment preferences and health status in elderly patients with higher-risk myelodysplastic syndromes. Issue 8 (August 2015) - Caocci, G.; Voso, M.T.; Angelucci, E.; Stauder, R.; Cottone, F.; Abel, G.; Nguyen, K.; Platzbecker, U.; Beyne-Rauzy, O.; Gaidano, G.; Invernizzi, R.; Molica, S.; et al.
Highlights: It is essential for physicians to focus attention on patient needs and preferences. Physicians' perceptions are frequently inconsistent with MDS patients' preferences. Physicians are poor judges of health status of their higher risk MDS patients. Decision aid-tools in the setting of higher-risk MDS might be helpful. Abstract: Higher-risk myelodysplastic syndromes (MDS) are rarely curable and have a poor prognosis. We investigated the accuracy of physicians' perception of patients' health status and the patients' preferences for involvement in treatment decisions. We examined 280 newly diagnosed higher-risk elderly MDS patients paired with their physicians. Survey tools included the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-Core 30 (EORTC QLQ-C30) and the Control Preference Scale. Overall concordance was 49% for physician perception of patient preferences for involvement in treatment decisions. In 36.4% of comparisons there were minor differences and in 14.6% there were major differences. In 44.7% of the patients preferring a passive role, physicians perceived them as preferring an active or collaborative role. Absence of the patient's request for prognostic information ( P  = 0.001) and judging the patient as having a poor health status ( P  = 0.036) were factors independently associated with the physicians' attitude toward a lower degree of patient involvement in clinical decisions. Agreement on health status was found in 27.5% of cases. Physicians most frequently tended to overestimate health status of patients who reported low-level health status. The value of decision aid-tools in the challenging setting of higher-risk MDS should be investigated to further promote patient-centered care.